Financial statement fraud strategies for detection and investigation - Zack, Gerard M. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
BValuable guidance for staying one step ahead of financial statement fraud/b Financial statement fraud is one of the most costly types of fraud and can have a direct financial impact on businesses and individuals, as well as harm investor confidence in the markets. While publications exist on financial statement fraud and roles and responsibilities within companies, there is a need for a practical guide on the different schemes that are used and detection guidance for these schemes. iFinancial Statement Fraud: Strategies for Detection and Investigation/i fills that need.ulliDescribes every major and emerging type of financial statement fraud, using real-life cases to illustrate the schemes/liliExplains the underlying accounting principles, citing both U.S. GAAP and IFRS that are violated when fraud is perpetrated/liliProvides numerous ratios, red flags, and other techniques useful in detecting financial statement fraud schemes/liliAccompanying website provides full-text copies of documents filed in connection with the cases that are cited as examples in the book, allowing the reader to explore details of each case further/li/ul Straightforward and insightful, iFinancial Statement Fraud/i provides comprehensive coverage on the different ways financial statement fraud is perpetrated, including those that capitalize on the most recent accounting standards developments, such as fair value issues.
Foreword -- Preface -- Acknowledgments -- Revenue-based schemes -- Introduction to revenue-based financial reporting fraud schemes -- Timing schemes -- Fictitious and inflated revenue -- Misclassification schemes -- Gross-up schemes -- Asset-based schemes -- Improper capitalization of costs -- Asset valuation schemes -- Fair value accounting -- Expense and liability schemes -- Shifting expenses to future periods -- Omissions and under-reporting of liabilities -- Other financial reporting schemes -- Consolidations and business combinations -- Financial reporting fraud as a concealment tool -- Financial statement fraud by not-for-profit organizations -- Disclosure fraud -- Detection and investigation -- Detecting financial statement fraud -- Financial statement analysis -- Ratio analysis -- Other detection procedures -- Fraud or honest mistake? -- Assessing (or minimizing) auditor liability.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Misleading financial statements; Fraud; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; BUSINESS & ECONOMICS -- Workplace Culture; Fraud; Misleading financial statements; Electronic books; Electronic books